Redemption Song: A Commentary on Caribbean Society - Maria Bacchus (Caribbean Studies Students' Union, 2023)
This essay unpacked and analyzed the seven-part documentary series, Redemption Song, narrated by Stuart Hall about the Caribbean in early 1990s. Given the diversity of the Caribbean, Redemption Song unified the Caribbean through its framing of how the Caribbean's past of foreign influence has shaped its present. Thus, this essay linked historical causality and the Caribbean's present as a cultural mosaic to argue that Redemption Song demonstrates how contemporary Caribbean society is a product of its history of foreign influence and colonialism. This was accomplished by discussing a scene from each episode of Redemption Song and connecting it with secondary literature on Caribbean society to touch upon how the series represents, and comments on, contemporary Caribbean society. Namely, this essay discussed issues concerning economy, identity, citizenship, race, class, sovereignty, borders, and tourism and how it has related British, African, Indian, French, Spanish, and American influences in the Caribbean.